Muvalaplin: A Novel Oral Therapy for Targeted Reduction of Plasma Lipoprotein(a) - Botros, Monica; Tiji, Michelle; Lange, Richard (Cardiovascular & Haematological Disorders - Drug Targets, 2026)
Plasma lipoprotein(a) [Lp(a)] levels greater than 50 mg/dL are an independent risk factor for cardiovascular diseases, including heart failure, atherosclerosis, and aortic valve stenosis. Lp(a) exhibits proatherogenic properties by promoting vascular inflammation, thrombosis, and calcification. Several therapeutic agents specifically designed to reduce Lp(a) formation are currently under evaluation in clinical trials or regulatory review. Muvalaplin is notable as the first orally administered drug developed to lower plasma Lp(a) levels. This review evaluates the efficacy, safety, and tolerability of muvalaplin and compares its profile with other Lp(a)-lowering agents. A systematic literature search was conducted using the PubMed database for articles published between 2020 and 2025, with keywords, including muvalaplin, lipoprotein, and cardiovascular. Only original research, clinical trials, and review articles were included. Muvalaplin is an oral small-molecule inhibitor being studied as the first oral Lp(a)-lowering agent. In Phase I trials, daily administration of muvalaplin for 14 days reduced Lp(a) levels by up to 65%. In Phase II trials, 12 weeks of daily muvalaplin resulted in reductions of up to 86% in Lp(a) levels without significant safety or tolerability concerns. These findings suggest that muvalaplin could be a valuable therapeutic option for managing cardiovascular risk associated with elevated Lp(a). Notably, unlike other Lp(a)-lowering agents, muvalaplin did not cause skin-related adverse events at injection sites. Although the initial clinical data are promising, Phase III trials are required to establish long-term safety and determine whether reductions in plasma Lp(a) translate into meaningful reductions in cardiovascular events.
Keywords: statin